Augmented Pressure Distal Colostogram. - Khalaf, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Anorectal malformations (ARMs) represent a complex group of congenital anomalies resulting from abnormal development of the hindgut, allantois and Mullerian duct, leading to incomplete or partial urorectal septal malformations . Patients and methods: This is a prospective study including sixty-five male patients with high ARMs who were admitted to the department of pediatric surgery in Children Welfare Teaching Hospital in Medical City Complex - Baghdad - Iraq ; during the period from April 2009 to November 2011 ; they were subjected to divided descending colostomy in the postnatal period ;Augmented-Pressure Distal Colostogram (APDC) was performed at a later age for demonstration of the level of rectal atresia and the presence of the recto-urinary fistulas which then were confirmed at operation. Objectives: The objective of this study is the accurate demonstration of the anatomy of the level of rectal atresia and any associated recto-urinary fistula by using APDC for optimal surgical management using APDC . Results: Rectourinary fistulas were demonstrated in 52 patients (80%) by APDC technique and were confirmed at operation in each case. In the remaining 13 patients (20%), this technique failed to demonstrate a fistula, in 8 of them no fistula was identified during operation or thereafter , while in the remaining 5 patients fistulas were detected during operation . Conclusion: The APDC readily demonstrated the level of the rectal atresia and the associated recto-urinary fistulas in the majority of the patients , providing a road map for definitive surgical repair of ARMs.